Bound State Solutions of Exponential-Coshine Screened Coulomb Plus Morse Potential (Journal of Atomic and Molecular Sciences, 2012)
The analytical solutions of the Schrödinger equation with exponential coshine screened plus Morse (ECSM) potential are presented. The energy eigenvalues and the corresponding eigenfunctions are obtained for several values of screening parameters.  We also present some numerical results for some selected diatomic molecules which are consistent with the values in the literature.
Keywords: Nikiforov-Uvarov method; energy eigenvalues; eigenfunctions diatomic molecules.